The European Society for Blood and Marrow Transplantation (EBMT) Consensus Guidelines for the Detection and Treatment of Donor-specific Anti-HLA Antibodies (DSA) in Haploidentical Hematopoietic Cell Transplantation. (May 2018) - Ciurea, Stefan; Cao, Kai; Fernandez-Vina, Marcelo; Kongtim, Piyanuch; Malki, Monzr; Fuchs, Ephraim; Luznik, Leo; Huang, Xiao-Jun; Ciceri, Fabio; Locatelli, Franco; Aversa, Franco; Castagna, Luca; et al.
Abstract Haploidentical donors are now increasingly considered for transplantation in the absence of HLA-matched donors or when an urgent transplant is needed. Donor-specific anti-HLA antibodies (DSA) have been recently recognized as an important barrier against successful engraftment of donor cells, which can affect transplant survival. DSA appear more prevalent in this type of transplant due to higher likelihood of alloimmunization of multiparous females against offspring's HLA antigens, and the degree of mismatch. Here we summarize the evidence for the role of DSA in the development of primary graft failure in haploidentical transplantation and provide consensus recommendations from the European Society for Blood and Marrow Transplant Group on testing, monitoring, and treatment of patients with DSA receiving haploidentical hematopoietic progenitor cell transplantation.